A Practical Algorithm for Determining the Optimal Pseudo-Boundary in the Method of Fundamental Solutions (Advances in Applied Mathematics and Mechanics, 2018)
One of the main difficulties in the application of the method offundamental solutions (MFS) is the determination of the position ofthe pseudo-boundary on which are placed the singularities in termsof which the approximation is expressed. In this work, we propose asimple practical algorithm for determining an estimate of thepseudo-boundary which yields the most accurate MFS approximationwhen the method is applied to certain boundary value problems.Several numerical examples are provided.